Activation of the transforming potential of p60c-src by a single amino acid change. - Levy, J B (1986)
Previous work showed that overexpression of the cellular src (c-src) gene does not cause transformation of chicken cells in culture. However, viral stocks isolated from cells transfected with Rous sarcoma virus DNA containing the c-src gene in place of the viral src gene did occasionally produce foci. Virus obtained from these foci were highly transforming and appeared to arise via spontaneous mutation in the c-src-containing viral populations. The p60 proteins of the transforming mutant src viruses were found to have higher levels of in vitro tyrosine kinase activity than the levels observed with the parental viruses. In this study, we have molecularly cloned the src DNA sequences of two transforming mutant src viruses. When compared to the DNA sequence of the parental c-src viruses, the mutant viruses contain single point mutations that result in single amino acid changes in the src gene products (p60 proteins). Both amino acid changes reside in the tyrosine kinase domain of the protein. The mutation detected in one virus involves replacement of the normal Glu-378 in p60c-src by Gly, whereas the p60 of the other transforming virus has Phe instead of the normal Ile-441. Our data indicate that when p60c-src is expressed at elevated levels in a retroviral context, a single amino acid change in its primary sequence can activate the kinase activity of this protein and cause cellular transformation.